Trophic State of The Sepinang Lake, Pangakalan Serik Village, Kampar Distric, Riau Province, Based on Nygaard Index. - Esmi Yanti br Sinaga; Madju Siagian; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Nygard Index can be used to determine the trophic state of waters. Calculation of this index is based on the number of phytoplankton species that are belonged to these following groups, namely Chlorococcales, Euglenophyceae, Centric diatom, Myxophyceae and Desmidiaceae. To understand the trophic state of the Sepinang Lake, a research has been conducted on March – April 2018. There were 3 sampling points, namely in the inlet, in the middle of the lake and in the end of the lake. In each sampling point, water samplet from the surface and 2 secchi depth. Sampling was done three times, once/week. Water quality parameters measured were phytoplankton, transparency, temperature, pH, nitrate, phosphate, Disolved oxygen and free carbondioxide. Results shown that there were 48 species of phytoplankton present, namely Desmidiaceae (10 species), Euglenophyceae (10 species), Chlorococcales order (14 species), Centric Diatom (5 species), and Class Mixophyceae (1 species). The water quality parameters were as follows: transparency49,3-63 cm, temperature 30,6–32,00;, pH 5.33-5.53, nitrate 0,08-0,17 mg/L, phosphate 0,10-0,18 mg/L, dissolved oxygen 4,63-5,04 mg/L, free carbon dioxide 11.32-13.32 mg/L. Nygaard Index value of the Sepinang Lake was 1.8-2.5, indicates that the Sepinang Lake is mesotrophic to eutrophic. Keywords : Oxbow Lake, Phytoplankton, Mesotrophic, Eutrophic.